The more, the better? Diversification Trends in Executive and Supervisory Boards in Germany and their Potential Effects - Bogdan Bedelev (Junior Management Science (JUMS), 2023)
In 2015, Germany passed the Gender Quota Law, and while some countries compelled listed companies to reserve at least 30% of their executive seats for women, imposing fines on the firms that failed to comply, Germany favoured soft-law quotas with almost no penalties. Additionally, this policy focused solely on supervisory board quotas and measures to counteract women's under-representation, neglecting other demographic and cognitive groups. Given the increasingly diverse population in Germany, it is necessary to study the role of other diversity dimensions in the board composition from the financial and social perspectives and whether there are any development trends in the German boards. In my Bachelor thesis, I study whether there are any diversity improvements in the composition of German-listed companies' executive and supervisory boards, presenting recent academic findings on the drivers and the effects of diverse boardrooms. Moreover, I conduct a descriptive analysis of the German board diversity trends, implementing a novel diversity index of Bernile et al. (2018) covering various diversity facets.
Keywords: 650; Controlling; Leadership; Board diversity; ESG; Corporate governance